Does potato seed system working effectively in Nepal? (Nepal Agriculture Research Journal, 2023)
The present study analyses the gaps and issues in the production and distribution system of potato seeds in Nepal. Households’ survey combined with focus group discussions (FGDs) and key informant interviews (KII) were carried out to collect the information. Gross benefit and descriptive statistics were employed for the analysis of the data. Results revealed that National Potato Research Program (NPRP) and some private companies were responsible for the zero generation Pre-Basic Seeds (PBS) production. National Centre for Potato, Vegetables and Spice Crops Development Program (NCPVSCDP) collects the seed demand and helps in potato seed certification at the farmers’ level. The current production is inadequate to meet the demand. As the present potato productivity is 16.72 mt ha-1 which is less than projected by National Seed Vision (NSV), reducing the yield gap is one of the important ways to meet the demand. The Gross benefit per hectare of first-generation basic potato seed (BS1) was NRs 14, 66,667 ($ 12,759) and second-generation basic potato seed (BS2) was NRs 9, 20, 667 ($ 8,009). However, the potato seed system is not working effectively in Nepal. Therefore, the adoption of improved potato varieties should be extensive through a strong mechanism for maintaining the full seed cycle and its proper distribution. Further, it is equally important to change the perception of farmers by showing the comparative benefit of growing ware potato and seed potato.